Piezotronic effect in AlGaN/AlN/GaN heterojunction nanowires used as a flexible strain sensor - Dong, Jianqi; Chen, Liang; Yang, Yuqing; Wang, Xingfu (Beilstein Journal of Nanotechnology, 2020)
1D semiconductor nanowires (NWs) have been extensively studied in recent years due to the predominant mechanical flexibility caused by a large surface-to-volume ratio and unique electrical and optical properties induced by the 1D quantum confinement effect. Herein, we use a top-down two-step preparation method to synthesize AlGaN/AlN/GaN heterojunction NWs with controllable size. A single NW is transferred to a flexible poly(ethylene terephthalate) substrate and fixed by indium tin oxide electrodes to form an ohmic contact for the strain sensor. An external mechanical stress is introduced to study the performance of the fabricated piezotronic strain sensor. The gauge factor is as high as 30 under compressive or tensile stress, which indicates a high sensitivity of the strain sensor. Periodic strain tests show the high stability and repeatability of the sensor. The working mechanism of the strain sensor is investigated and systematically analyzed under compressive and tensile strain. Here, we describe a strain sensor that shows a great application potential in wearable integrated circuits, in health-monitoring devices, and in artificial intelligence.
Keywords: AlGaN/AlN/GaN nanowires; flexible; piezotronic effect; strain sensors; strain tests; top-down method